ADVERSATIVE CONJUNCTION IN HEALTH ARTICLE ENTITLE COVID-19: NOT ALL HAND SANITIZERS WORK AGAINST IT – HERE’S WHAT YOU SHOULD USE - Dewi, Ni Luh Desy Suari; Wardhana, I Gede Neil Prajamukti; Utami, Gek Wulan Novi (LITERA : Jurnal Bahasa Dan Sastra, 2021)
ABSTRACTAn article will have a good texture if it has good coherence. An article has a coherence whenthe ideas of the article are related one to another. The coherence of the article can be supportedby the use of a conjunction. Based on the assumption that conjunction takes an important rolein a text, it will be interested to discuss conjunction in an article. The discussion will be focusedon how the author contrasts the information or his opinion. The collected data in this writingwere qualitatively analyzed by using the theory of conjunction proposed by Halliday andHasan. The analysis was started by analyzing the types of adversative conjunction in the healthan article. Then, it continued by describing how these types of adversative conjunction contrastthe idea or information in the article. Based on the analysis, the adversative conjunctions thatcan be found are (1) though, (2) but, (3) only, (4) however, (5) rather and (6) instead. Thecontrasting can be shown by giving further information, by against the statement, by givingcorrection or replacing one thing to the other.Key Word: Conjunction, Adversative Conjunction, ArticleABSTRAKSebuah artikel akan memiliki bentuk yang baik jika memiliki koherensi yang baik. Sebuahartikel dapat dikatakan memiliki koherensi ketika ide-ide dalam artikel tersebut saling terkaitsatu sama lain. Koherensi di dalam sebuah artikel dapat didukung oleh penggunaan katahubung. Berdasarkan asumsi bahwa kata hubung mengambil peran penting dalam sebuah teks,maka dalam analisis ini akan dibahas tentang kata hubung dalam sebuah artikel. Diskusi akandifokuskan pada bagaimana penulis membedakan informasi atau dalam artikel. Data yangdikumpulkan dalam tulisan ini dianalisis secara kualitatif dengan menggunakanteori conjunction yang diajukan oleh Halliday dan Hasan. Analisis ini dimulai denganmenganalisis jenis adversative conjunction dalam sebuah artikel. Kemudian, dilanjutkandengan menjelaskan bagaimana jenis-jenis adversative conjunction ini digunakan untukmembedakan ide atau informasi dalam artikel. Berdasarkan analisis, adversative conjunctionyang dapat ditemukan adalah (1) though, (2) but, (3) only, (4) however, (5) rather and (6)instead. Untuk menunjukkan perbedaan ide atau informasi dalam artikel dapat ditunjukkandengan memberikan informasi lebih lanjut, dengan menentang pernyataan tersebut, denganmemberikan koreksi atau mengganti satu hal dengan yang lain.Kata kunci: Konjungsi, Adversative conjunction, Artikel